Rancang Bangun Perangkat IoT untuk Pengendalian Pakan Pada Budidaya Ikan Hias Cupang (Betta Fish) - Marwondo Marwondo; Sarjono Sarjono; Iqbal Ardiansyah (Ma'soem University, 2023)
Betta fish are one of the favorite ornamental fish which is much loved because of its beauty. This is the reason why so many people want to cultivate it. During the cultivation period, farmers are often negligent in providing fish with a feeding schedule. Quite a few cultivators also pay less attention to dosage, feed size, temperature and pH levels when feeding baby betta fish, which results in waste and neglect of the environmental health of cultivation ponds. Controlling the correct dosage, size and feeding schedule according to the age of the baby fish, temperature and water pH will be able to increase the success of cultivation. Controlling the dosage, size and schedule of feed can actually be done automatically with the realization of IoT devices. This device was built through co-create, ideate, Q&A IoT OSI, and prototype so that this device can run well. This device uses an Arduino Uno R3 SMD as a microcontroller, a DS18B20 sensor as a temperature sensor, and a pH sensor connected to a servo motor to control the feed dispenser. The Arduino Uno R3 was chosen because of its wide compatibility with various sensors as well as the flexibility to write our own program code. Water temperature and pH sensors are used to monitor environmental conditions in real-time which will be used to make intelligent decisions regarding feeding. This device will put food into the pond according to the schedule, dosage and size of the food based on the water temperature and pH conditions. As a monitoring screen, thingspeak is used as a dashboard which can be accessed online via a web browser. Based on several experiments carried out, this IoT device is able to provide good feed dosage accuracy according to the needs of young fish, making it easier for farmers to care for fish without their physical presence. This research contributes to the development of IoT in the context of fish farming which can increase the success of cultivation and the welfare of farmers.